‘Don’t Blow Your Cool’: Provocation, Violent Coping, and the Conditioning Effects of Self-Control - Schulz, Sonja (Journal of quantitative criminology, 2016)
Objectives General Strain Theory (Agnew in Criminology 30:47–87, 1992 ) has received broad empirical support, but little is known about moderators of the strain-delinquency relationship. This study tests whether self-control attenuates the relationship between a certain type of delinquency—violence—and its most important precursor, considered a type of strain: interpersonal provocation. This study compares the conditioning effects of risk-affinity and self-control/impulsivity on the provocation-violence link, since recent work suggests differentiating between both characteristics. Methods The provocation-violence link is examined (1) using a scenario design with randomly varied degrees of objective provocation and a measure of projected violence, and (2) with measures of self-reported past violence and subjective sensitivity to provocation. The analyses are based on a large sample of seventh-graders (n = 2635) from five cities in Western Germany, interviewed in 2013. Linear probability models regressing violence measures on personal traits, provocation measures, and their interactions are estimated. Results Both self-control and risk-affinity moderate the relationship between subjective sensitivity to provocation and past violent behavior. Students with high self-control are able to control their anger and do not turn violent, even when they feel provoked easily. However, only risk-affinity significantly amplifies the effect of objective provocation on prospective violence when simultaneously controlling for the conditioning effect of self-control. Conclusions Findings underscore that both self-control and risk-aversion are important coping resources. This study highlights the importance of using internally consistent and mechanism-congruent measures in the study of illicit coping processes and conditioning factors and discourages from using composite, potentially multidimensional measures.